2020
DOI: 10.1007/s00392-020-01760-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk predictors in atrial fibrillation patients following successful coronary stenting: ENTRUST-AF PCI sub-analysis

Abstract: Aims This subgroup analysis of the ENTRUST-AF PCI trial (ClinicalTrials.gov Identifier: NCT02866175; Date of registration: August 2016) evaluated type of AF, and CHA2DS2-VASc score parameters as predictors for clinical outcome. Methods Patients were randomly assigned after percutaneous coronary intervention (PCI) to either edoxaban (60 mg/30 mg once daily [OD]; n = 751) plus a P2Y12 inhibitor for 12 months or a vitamin K antagonist [VKA] (n = 755) plus a P2Y12 inhibitor and aspirin (100 mg OD, for 1–12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…These changes are not related to the presence of absence of AF, explaining why atrial thrombogenesis is still increased even during sinus rhythm in certain subgroups of patients [211,212]. Recently, post hoc studies from large randomized controlled trials suggested that the burden of AF (Figure 3) as well as the type of AF (paroxysmal versus persistent/permanent AF) might be a factor, which drives differences in patient outcome [213][214][215][216][217]. Such clinical differences might be explained at least to some extent by differences in atrial cardiomyopathies and ventricular oxidative stress levels during various types of AF [210].…”
Section: Atrial Endocardial Remodeling As a Cause Of Thrombogenesis And Strokementioning
confidence: 99%
“…These changes are not related to the presence of absence of AF, explaining why atrial thrombogenesis is still increased even during sinus rhythm in certain subgroups of patients [211,212]. Recently, post hoc studies from large randomized controlled trials suggested that the burden of AF (Figure 3) as well as the type of AF (paroxysmal versus persistent/permanent AF) might be a factor, which drives differences in patient outcome [213][214][215][216][217]. Such clinical differences might be explained at least to some extent by differences in atrial cardiomyopathies and ventricular oxidative stress levels during various types of AF [210].…”
Section: Atrial Endocardial Remodeling As a Cause Of Thrombogenesis And Strokementioning
confidence: 99%
“…Interestingly, sub-analyses of the ENTRUST-AF and ENSURE-AF trials showed an association of MI and PAF not observed in patients with persistent AF [13,14]. The authors propose that PAF is associated with microcirculatory flow abnormalities and may increase events in vulnerable myocardium [13,14]. However, several limitations may limit the generalization of the findings.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, a meta-analysis of 12 studies, with almost 100.000 patient showed that NPAF was associated with a higher risk for thromboembolism and all-cause mortality, no difference in bleeding was observed [11]. Interestingly, sub-analyses of the ENTRUST-AF and ENSURE-AF trials showed an association of MI and PAF not observed in patients with persistent AF [13,14]. The authors propose that PAF is associated with microcirculatory flow abnormalities and may increase events in vulnerable myocardium [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a patient with AF requires PCI with consecutive DAPT, combining ASA + OAC + clopidogrel can increase the risk of bleeding by 3–4-fold compared to OAC alone [ 10 , 40 ]. Thus, there had been a quest for alternative anti-thrombotic combination therapies with less bleeding risk.…”
Section: Incremental Harm Of Conventional Triple Anti-thrombotic Therapymentioning
confidence: 99%